13C NMR Characterization of Triacylglycerides of Roodbar and Tarem Olive Oils of Iran and Comparison with Commercial Olive Oil of Olitalia (Italia) and Luna (Turkey) - O. Mahmoodi, Nosrat; Sharif Zadeh, Bahman (Asian Journal of Chemistry, 2010)
The 13C NMR spectroscopy for study and characterization of crude olive oils of Roodbar and Tarem regions of Iran and comparing them with commercial samples of Olitalia from Italia and Luna from Turkey was utilized. The separation of oleic acid of these olive oils was subjected to detailed analysis by urea inclusion complex techniques.